Arabidopsis HISTONE DEACETYLASE 9 Stimulates Hypocotyl Cell Elongation by Repressing GIGANTEA Expression Under Short Day Photoperiod - Lee, Hong Gil; Jeong, Yeong Yeop; Lee, Hongwoo; Seo, Pil Joon (Frontiers in Plant Science, 2022)
Developmental plasticity contributes to plant adaptation and fitness in a given condition. Hypocotyl elongation is under the tight control of complex genetic networks encompassing light, circadian, and photoperiod signaling. In this study, we demonstrate that HISTONE DEACETYLASE 9 (HDA9) mediates day length-dependent hypocotyl cell elongation. HDA9 binds to the GIGANTEA (GI) locus, which is known to be involved in photoperiodic hypocotyl elongation. The short day (SD)-accumulated HDA9 protein promotes histone H3 deacetylation at the GI locus during the dark period, promoting hypocotyl elongation. Consistently, HDA9-deficient mutants display reduced hypocotyl length, along with an increase in GI gene expression, only under SD conditions. Taken together, our study reveals the genetic basis of day length-dependent cell elongation in plants.